Passionate bricoleurs and new venture survival - Stenholm Pekka; Renko Maija (Elsevier, 2022)
The impression of entrepreneurship as an intentionally orchestrated activity has been challenged by more creative approaches. In this study we investigate the previously unexplored relationships between entrepreneurial passion, bricolage, and entrepreneurial survival. In a sample of 2489 Finnish entrepreneurs who started new businesses between 2005–2010, we find higher levels of bricolage among those, whose businesses were still surviving in the end of 2011. Further, our analyses reveal that entrepreneurs who are passionate about inventing and developing their ventures are more likely to engage in bricolage and, combined, the affective state of passion and the “make-do” behaviors of bricolage help entrepreneurs keep their businesses going.